2023
DOI: 10.5194/egusphere-2023-402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low Cobalt Inventories in the Amundsen and Ross Seas Driven by High Demand for Labile Cobalt Uptake Among Native Phytoplankton Communities

Abstract: Abstract. Cobalt (Co) is a scarce but essential micronutrient for marine plankton in the Southern Ocean and coastal Antarctic seas where dissolved cobalt (dCo) concentrations can be extremely low. This study presents total dCo and labile dCo distributions measured via shipboard voltammetry in the Amundsen Sea, Ross Sea and Terra Nova Bay during the CICLOPS (Cobalamin and Iron Co-Limitation of Phytoplankton Species) expedition. A significantly smaller dCo inventory was observed during the 2017/2018 CICLOPS expe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(126 reference statements)
1
0
0
Order By: Relevance
“…While Zn speciation was not measured in this study, it is likely that Zn organic complexation further depleted total bioavailable Zn. A concurrent study of Co speciation observed complete complexation of dissolved Co in the upper water column in TNB, consistent with this idea 39 . Consistent with high macronutrient abundance in this region (as observed previously and in the present study; Supplemental Figure 1b,c,d ), surface macronutrient concentrations (nitrate and nitrite, phosphate, and silicic acid) were partially depleted at the experimental site with 64%, 46%, and 29% decreases in N+N, P, and Si, respectively, comparing 10 m and average deep water (200 – 1000 m) values ( Supplementary Figure 3d ).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…While Zn speciation was not measured in this study, it is likely that Zn organic complexation further depleted total bioavailable Zn. A concurrent study of Co speciation observed complete complexation of dissolved Co in the upper water column in TNB, consistent with this idea 39 . Consistent with high macronutrient abundance in this region (as observed previously and in the present study; Supplemental Figure 1b,c,d ), surface macronutrient concentrations (nitrate and nitrite, phosphate, and silicic acid) were partially depleted at the experimental site with 64%, 46%, and 29% decreases in N+N, P, and Si, respectively, comparing 10 m and average deep water (200 – 1000 m) values ( Supplementary Figure 3d ).…”
Section: Resultssupporting
confidence: 60%
“…While Zn speciation was not measured in this study, it is likely that Zn organic complexation further depleted total bioavailable Zn. A concurrent study of Co speciation observed complete complexation of dissolved Co in the upper water column in TNB, consistent with this idea 39 .…”
Section: Biogeochemical Characterization Of the Incubation Study Sitesupporting
confidence: 60%